INVISIBLE CITIES: THE TABLE OF CONTENTS AND THE LABYRINTHS OF REALITY - Serravalle de Sá, Daniel (2019)
In Invisible Cities (1972), Italo Calvino contrasts a rigid outline structure with a flexible textual content. The tension comprised by the numerical structure proposed in the table of contents stands out against the set of polissemic texts which make up the subject matter of the book. The opposition between form and content point to a fruitful dichotomy in the conception of the novel linked to the theories of the open and closed work. This essay will investigate the structural construction of Invisible Cities by looking at its table of contents, seeking to discuss some models of formalistic representation proposed by the criticism and the specific contribution they may, or may not, provide. The objective is to analyse the pertinence of such theories in the light of historical and cultural approaches. Aiming to uncover possible meanings which arise from the debate, this essay will question to what extent structural complexities can be considered literary if they are not ultimately related to the culture in which a text is found.